Advances in Behavioral Remote Data Collection in the Home Setting: Assessing the Mother-Infant Relationship and Infant’s Adaptive Behavior via Virtual Visits - Shin, Eunkyung; Smith, Cynthia L.; Howell, Brittany R. (Frontiers in Psychology, 2021)
Psychological science is struggling with moving forward in the midst of the COVID-19 pandemic, especially due to the halting behavioral data collection in the laboratory. Safety barriers to assessing psychological behavior in person increased the need for remote data collection in natural settings. In response to these challenges, researchers, including our team, have utilized this time to advance remote behavioral methodology. In this paper, we will provide an overview of our group’s strategies for remote data collection methodology and examples from our research in collecting behavioral data in the context of psychological functioning. Then, we will describe the design and development of our remote data collection of mother-infant interactions, with the goal being to assess maternal sensitivity and intrusiveness as well as infants’ adaptive behaviors in several developmental domains. During these virtual visits over Zoom, mother-infant dyads watch a book-reading video and are asked to participate in peek-a-boo, toy play, and toy removal tasks. After the behavioral tasks, a semi-structured interview (Vineland Adaptive Behavior Scale - VABS III) is conducted to assess the infant’s adaptive behavior in communication, socialization, daily living skills, and motor domains. This paper will delineate the specific strategies we are currently applying to integrate laboratory tasks and a semi-structured interview into remote data collection in home settings with mothers and infants. We will also elaborate on issues encountered during remote data collection and how we resolved these challenges. Lastly, to inform protocols for future remote data collection, we will address considerations and recommendations as well as benefits and future directions for behavioral researchers in developmental psychology research.